Sterol metabolism of pacific oyster (Crassostrea gigas) spat - Knauer, J; Kerr, R G; Lindley, D; Southgate, Paul C (Comparative Biochemistry and Physiology Part B: Biochemistry and Molecular Biology, 1998)
The sterol metabolism of Pacific oyster (Crassostrea gigas) spat was investigated. 3H-squalene, 3H-desmosterol and 3H-fucosterol were mixed with oleic acid and separately encapsulated in gelatin-acacia microcapsules (GAM). Spat were fed one type of GAM for 7 days and were then unfed for 2 days. No labeled sterols were detected in spat fed GAM containing 3H-squalene, demonstrating the absence of de novo sterol synthesis in C. gigas spat. 3H-desmosterol, a C27 sterol, was alkylated to the C28 sterols 24-methylenecholesterol and 24 methylcholesterol and was also reduced to cholesterol. In spat fed GAM containing 3H-fucosterol, a C29 sterol, radioactive desmosterol and cholesterol (C27 sterols) and radioactive 24-methylenecholesterol and 24-methylcholesterol (C28 sterols) were recovered. These results demonstrate that C. gigas spat is capable of both alkylation and dealkylation of dietary sterols.